Dimorfismo Sexual na Hipertrofia Ventricular Esquerda e Função cardíaca de Ratos Espontaneamente Hipertensos: O Papel da Atividade da Enzima Conversora de Angiotensina (ECA) e ECA2 no Ventrículo Esquerdo e no Rim - Dalpiaz, Polyana Lima Meireles (2015)
Abstract There is growing interest in sex differences and RAS components; however, whether gender influences cardiac angiotensin I-converting enzyme (ACE) and angiotensin-converting enzyme 2 (ACE2) activity is still unknown. In the present work we determined the relationship between ACE and ACE2 activity on kidney and heart, left ventricular function and gender in spontaneously hypertensive rats (SHRs). Twelve-week-old female (F) and male (M) SHRs were divided into 2 experimental groups (n = 7 in each group): sham (S) and gonadectomized (G). Fifty days after gonadectomy, we measured positive and negative first derivatives (dP/dt+ and dP/dt-), hypertrophy (morphometric analysis) and ACE and ACE2 catalytic activity in kidney and LV (left ventricle). Expression of calcium handling proteins and AT1 receptor was measured by western blot analysis. Male rats exhibited higher cardiac ACE and ACE2 activity as well as hypertrophy compared to female rats. Orchiectomy reduced ACE activity and hypertrophy, while ovariectomy increased these variables. In relation to cardiac function, the sham group, male to compared female rats, had a lower +dP/dt (MS: 5140 ± 259 mmHg vs. FS: 6485 ± 178 mmHg) and lower -dP/dt (MS: -3.717 ± 129 mmHg vs. FS: -5.250 ± 115 mmHg) than the female sham group. After gonadectomy, the results inverted such that they were increased in males and reduced in female rats in dP/dt+ (GM = 6.728 ± 177 mmHg vs FG: 5453 ± 229 mmHg) and dP/dt- (SM: -4.851 ± 290 mmHg vs GF = -3.913 ± 136 mmHg). No difference among the groups in the SERCA2a protein expression was observed. The gonadectomy increased protein expression of PLB and the PLB to SERCA2a ratio in female rats, but did not alter in male rats. In conclusion, the ovariectomy leads to increased cardiac hypertrophy, ACE2 activity, PLB expression and PLB to SERCA2a ratio, and worsening of hemodynamic variables, wher-eas in males the removal of testosterone has the opposite effect in RAS components. Our data suggest that sex steroids are of great importance for both female and male SHRs in influencing cardiac function and in regulating the RAS in kidney and LV. In our study, in LV the withdrawal of estrogen in females led to increased cardiac hypertrophy, increased ACE2 activity, PLB expression and PLB to SERCA2a ratio, what could be related to worsening of hemodynamic variables. In males, however, the removal of testosterone had the opposite effect in RAS components. The increase in ACE2 activity after ovariectomy and the reduction after orchiectomy seems to be occurring to counterbalance the observed changes. In the kidney, in females the activity of ACE and ACE2 was higher, favoring the balance between these two important components of the RAS. In the male, conversely, lower levels of ACE and ACE2 favoring the imbalance. ACE, although important, has not changed with the hormonal status, so that in this model, the ACE2 have greater involvement in local modulation of these components. Certainly, the assessment of sexual dimorphism of the components of the RAS can help the continued development of effective therapeutic interventions for cardiovascular diseases.